Relationship Between Inflow Impairment and Skin Oxygen Availability to the Upper Limb During Standardized Arm Abduction in Patients With Suspected Thoracic Outlet Syndrome - Hersant, Jeanne; Lecoq, Simon; Ramondou, Pierre; Papon, Xavier; Feuilloy, Mathieu; Abraham, Pierre; Henni, Samir (Frontiers in Physiology, 2022)
Objective: Thoracic outlet syndrome (TOS) should be considered of arterial origin only if patients have clinical symptoms due to documented symptomatic ischemia. Simultaneous recording of inflow impairment and forearm ischemia in patients with suspected TOS has never been reported to date. We hypothesized that ischemia would occur only in case of severely impaired inflow, resulting in a non-linear relationship between pulse amplitude (PA) changes and estimation of ischemia during provocative attitudinal upper limb positioning. Design: Prospective single center interventional study Material: Fifty-five patients with a suspicion of thoracic outlet syndrome Methods: We measured the minimal decrease from rest of transcutaneous oximetry pressure (DROPm) as an estimation of oxygen deficit and arterial pulse plethysmography to measure pulse amplitude changes from rest (PA-change) on both arms during the candlestick phase of a “Ca+Pra” maneuver. “Ca+Pra” is a modified Roos test allowing the estimation of maximal PA-change during the “Pra” phase. We compared the DROPm values between categories of PA-change with ANOVA. Then, we analyzed the relationship between PA-change and DROPm with linear and non-linear models. Results are reported as median [25/75 centiles]. Statistical significance was p < .05. Results: DROPm values ranged -11 [-7 / -19] mmHg and PA-change ranged 35 [4/65] in the 44 arm values. DROPm was -28 [-22/-37] mmHg for PA-change<0, -9 [-7/-19] mmHg for PA-change 0 to 50%, and -7[-5/-12] mmHg for PA-change> 50%: p<.05 between PA-change<0 and the other 2 groups. The relationship between DROPm and PA-change was .652 with a polynomial fitting but only .583 with a linear approach. Conclusion: Oxygen availability was decreased only in the cases of severe but not moderate attitudinal inflow impairments. Simultaneous A-PPG and forearm oximetry during the ”Ca+Pra” maneuver is an interesting approach for providing objective proof of ischemia in patients with symptoms of TOS suspected of arterial origin.